Características do ensino de astronomia nos cursos de licenciatura em física dos Institutos Federais de Educação Ciência - Paganotti, Arilson (2020)
Since antiquity, man has been interested in the mysteries of the sky and the Universe, and the curiosity that Astronomy provokes in people is notorious. In schools, Astronomy can be used with students as a means of scientific dissemination, awakening their interest in Natural Sciences. In this work, a research was carried out that investigates the characteristics of the Physics teacher training courses at the Federal Institutes, with emphasis on the Teaching of Astronomy/Physics developed in these courses. The research took place in two stages. The first was based on a study with the Federal Institutes that offer Physics Degree courses, based on the documentary analysis of the Pedagogical Project of the courses. The second stage consisted of analyzing the responses of the course coordinators, given to an online questionnaire, previously prepared on the Google Forms platform. The research was guided by a qualitative study based on the documentary analysis of the Pedagogical Projects of the Courses, followed by a qualitative and quantitative study based on categorizations carried out based on the content analysis of the questionnaire responses applied to the course coordinators. Some results pointed out that in the Federal Institutes Astronomy is used both on campuses that offer Degree courses in Physics and on other campuses, which do not have this type of course, however, they develop scientific dissemination projects with the use of optical equipment such as binoculars, telescopes and telescopes. It was also found that out of the total of 585 campuses of the Federal Institutes, spread across the country, only 74 offer Degree courses in Physics. Other aspects, such as the presence of specific Astronomy subjects or subjects that use Digital Information and Communication Technologies in the curricular matrix of the courses, were also observed. Among the coordinators surveyed, it was noticed that they understand the need to work on Astronomy in the Physics Degree course and even though there is no specific discipline on the subject, this topic can be worked through other academic activities. This research presented a global context of Teaching Astronomy/Physics and the characteristics associated with the initial training courses for Physics teachers at Federal Institutes. It is hoped that it will serve as a source for further research and provide relevant information on the way in which Astronomy/Physics Teaching occurs in these institutions of the Federal Network of Professional, Scientific and Technological Education.